2021
DOI: 10.1002/2211-5463.13044
|View full text |Cite
|
Sign up to set email alerts
|

A loss‐of‐function mutation p.T256M in NDRG4 is implicated in the pathogenesis of pulmonary atresia with ventricular septal defect (PA/VSD) and tetralogy of Fallot (TOF)

Abstract: A loss-of-function mutation p.T256M in NDRG4 is implicated in the pathogenesis of pulmonary atresia with ventricular septal defect (PA/VSD) and tetralogy of Fallot (TOF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Highlighting the genetic variability of TOF; 16 additional patients have been identified to have one pathogenic/likely pathogenic variant (11 loss of function and five missense) in 16 CHD genes ( ARHGAP31, ATRX, CACNA1C, CHD7, CSNK2A1, DLL4, EP300, GATAD2B, KAT6A, LZTR1, NF1, NODAL, PIK3CA, RAF1, RASA1, and SMAD2 ) and one patient has been identified with loss of function variants in two genes ( ASXL1 and PSMD12 ) ( Reuter et al, 2019 ). In addition, recent studies have shown that new variants found in TOF cases in the NDRG4 gene cause multiple heart abnormalities ( Peng et al, 2021 ). Evidence suggests that SMARCC2 is required for cardiac development by promoting cardiac myocyte differentiation and controlling temporal steps in cardiac differentiation ( Hota et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting the genetic variability of TOF; 16 additional patients have been identified to have one pathogenic/likely pathogenic variant (11 loss of function and five missense) in 16 CHD genes ( ARHGAP31, ATRX, CACNA1C, CHD7, CSNK2A1, DLL4, EP300, GATAD2B, KAT6A, LZTR1, NF1, NODAL, PIK3CA, RAF1, RASA1, and SMAD2 ) and one patient has been identified with loss of function variants in two genes ( ASXL1 and PSMD12 ) ( Reuter et al, 2019 ). In addition, recent studies have shown that new variants found in TOF cases in the NDRG4 gene cause multiple heart abnormalities ( Peng et al, 2021 ). Evidence suggests that SMARCC2 is required for cardiac development by promoting cardiac myocyte differentiation and controlling temporal steps in cardiac differentiation ( Hota et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have conducted many disease-oriented population sequencing experiments and further improved in vitro and in vivo experiments to screen-out suspected pathogenic genes and mutation sites. We reported several pathogenic genes and variants associated with CHD, including SOX7 , [75] TBX1 , [76] NDRG4 , [77] and FOXH1 . [78] The data are helpful for the establishment of genes and phenotypes database of the Chinese population, and provide a basis for precise clinical diagnosis of CHD etiology.…”
Section: Construction Of Xinhua Intrauterine Diagnosis Systemmentioning
confidence: 99%
“… 12 Peng et al have revealed that the p.T256M variant in NDRG4 is a pathogenic variant associated with the impaired proliferation of human cardiomyocytes and cell cycle arrest, which may be involved in the pathogenesis of VSD. 13 Taken together, genetic factors are crucial in the occurrence of VSD. However, some genetic variants associated with VSD in the Chinese Tibetan population remain to be further identified.…”
Section: Introductionmentioning
confidence: 99%